THE THIRD SECTOR, THE SOCIAL ECONOMY AND SOCIAL WORK IN COSTA RICA - Quesada, Ana Cristina (2013)
In the last decades, severals international organizations have an interest to re-formulate, in a scientific and politicaly way, the organizational propose of the “Third Sector”and “Social Economy”. This article shows a vision of the origins, features and manifestations of the “Third Sector” and “Social Economy” in Costa Rica, how the different professionals of Social Work have been involved with the organizations of the “Third Sector” in the national environment.